Utilization of Silver Nanoparticles as Adsorbent of Methylene Blue - Susanto, Nindita Clourisa Amaris; Fajri, Nadiatul; Pratama, Yoga; Prasetio, M. Reza; Rahayu, Rahayu; Hapsari, Aulia Ratri (Walisongo Journal of Chemistry, 2023)
This study has successfully synthesized silver nanoparticles (Ag NPs) using banana stem extract as the bioreductor and reported its application in adsorption of methylene blue (MB). Adsorption of MB was tested under ultraviolet light by varying pH solution values (3, 4, 5, 7, 9, 10, and 11), irradiation times (0,5, 1, 2, 3, 4, 5 hours), and MB concentrations (50, 100, 150, and 200 ppm) to determine their optimum values. The results revealed that the optimum pH value and irradiation time were at 9 and 1 hour, demonstrating the highest deconcentration percentage (%D) of 89.19% and 94.58%, respectively. The %D of MB dye by samples with concentrations of 50, 100, 150, and 200 ppm were 86.294%, 78.416%, 69.366%, and 66.638%, respectively, with an average of %D of 75.189%. The least degraded MB was 90.643 mg, obtained at 50 ppm. Meanwhile, the most degraded MB was 280.181 mg, attained at 200 ppm. The average concentration of degraded MB was 188.538 mg/gr.